Awareness of Human Resource Accounting Practices and Costing: Evidence from the Philippines - Ibarra, Venus C (Archīum Ateneo, 2017)
This study focused on the awareness of the Human Resource Accounting Practices and Costing (HRAC) of companies located in Carmelray Industrial Park 1 (CIP 1), Canlubang, Calamba City. The respondents were 8 human resource managers, 18 human resource supervisors, 8 finance officers, 9 chief accountants, and 5 accounting supervisors of the forty-eight (48) companies of CIP 1. The researchers used a questionnaire to collect the data. The study disclosed that the companies were not aware of the HRAC Cost Based Approach Models. The results also revealed that CIP 1 companies used the traditional or conventional accounting for human resources, where costs incurred for human resources were charged to expenses. The level of awareness and acceptance of the forty-eight companies of CIP 1 is very low. Based on the findings, the researchers recommended an accounting system that the companies might be able to use.